Learning Media In Mathematics Education: A Bibliometric Analysis - Awal Kurnia Putra Nasution; Leni Agustina Daulay; Nurul Qomariyah Ahmad (Universitas Muhammadiyah Enrekang, 2023)
This bibliometric analysis investigates the development of instructional media in mathematics education. As mathematics education is crucial for various fields, including science, technology, economics, and business, identifying effective learning media is essential to improve the quality of mathematics learning. This bibliometric analysis examines the trends, subject areas, and types of documents related to the use of instructional media in mathematics education. Results show an increasing trend in publications, with conference papers and scientific journal articles being the most common document types. The study highlights the importance of considering factors related to the learning environment, student involvement, and achievement when developing effective learning media, especially online learning during the Covid-19 pandemic. The findings provide insights for mathematics educators, researchers, and policymakers to improve mathematics learning quality and suggest further research directions.